2017
DOI: 10.1097/psy.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Posterior Insular Volume in Adolescent Anorexia Nervosa

Abstract: Objective The diagnostic criterion disturbance in the experience of the body remains a poorly understood and persistent feature of anorexia nervosa (AN). Increased sophistication in understanding the structure of the insular cortex - a neural structure that receives and integrates visceral sensations with action and meaning - may elucidate the nature of this disturbance. We explored age, weight-status, illness severity, and self-reported body dissatisfaction associations with insular cortex volume. Methods S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
0
8
1
Order By: Relevance
“…Moreover, the sensory aspects of taste are primarily an insula-related phenomenon, whereas higher cortical areas modulate pleasure, motivation, and cognitive aspects of taste [53,54,55]. It is worth noting that the laterality of our findings differs from the study by Zucker et al [26], where an altered structure of the right posterior insular cortex was detected. A possible explanation for this difference could be based on the underlying imbalance in the network implicating both insular cortices, as previously suggested [56].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Moreover, the sensory aspects of taste are primarily an insula-related phenomenon, whereas higher cortical areas modulate pleasure, motivation, and cognitive aspects of taste [53,54,55]. It is worth noting that the laterality of our findings differs from the study by Zucker et al [26], where an altered structure of the right posterior insular cortex was detected. A possible explanation for this difference could be based on the underlying imbalance in the network implicating both insular cortices, as previously suggested [56].…”
Section: Discussioncontrasting
confidence: 81%
“…A GM reduction of the insula could reflect disturbances in the limbic system, which is involved in interoceptive deficit [51], body dissatisfaction, and low self-esteem. The insular cortex represents a node of convergence for signals composing emotional and cognitive states, which emerge from the coordination between external and internal milieus, and mediating frontotemporal interaction in social and emotional context processing [25,26,52]. Moreover, the sensory aspects of taste are primarily an insula-related phenomenon, whereas higher cortical areas modulate pleasure, motivation, and cognitive aspects of taste [53,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is argued that the anterior insula, alongside the amygdala, nucleus accumbens and orbitofrontal cortex are key to supporting our conscious awareness of emotion and integrating this with our sense of self ( Seth, 2013 ). Further, the posterior insula receives and encodes visceral interoceptive input, and increased right posterior insular volume correlates with disorder duration and severity in AN suggesting that difficulties in integrating bottom-up interoceptive information increase with length of disorder ( Zucker et al, 2017 ). Moreover, patterns of insula responding to unpleasant interoceptive states are significantly different for those in remission from AN versus healthy comparison participants ( Berner et al, 2018 ).…”
Section: Perpetuation Of An: the Ever Decreasing ‘Self’mentioning
confidence: 99%
“…Several interoceptive alterations have been found in AN and neuroimaging evidence suggested that this pathology can compromise numerous key cortical structures within the interoceptive network. Specifically, AN subjects exhibited white matter abnormality and altered resting state functionality (Gaudio et al, 2015, 2017) of the anterior cingulate cortex (ACC), along with volume reduction of the right posterior insular cortex (Zucker et al, 2017) also in weight-restored AN patients (Kerr et al, 2016). Besides, AN alterations are not only limited to neurophysiological levels.…”
Section: Introductionmentioning
confidence: 99%